2019
DOI: 10.1002/chem.201903482
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Halogen Coordination Effect of Stable Bimetallic MOFs on Oxygen Evolution Reaction

Abstract: The energy crisis and environmental pollution have forced scientists to explore alternative energy conversion and storage devices. The anodic reactions of these devices are all oxygen evolution reactions (OER), so the development of efficient OER electrocatalysts is of great significance. At the same time, understanding the reaction mechanism of OER is conducive to the rational design of efficient OER electrocatalysts. In general, catalytic active centers play a direct role in OER performance. In this paper, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…4F). On the basis of the aforementioned electrocatalytic performance results, the Br-Ni-MOF hollow prisms manifest excellent OER performance with a low  10 , a small Tafel slope, and high TOF values after an in situ activation process, serving as one of the most efficient MOF-based or MOF-derived (oxy)hydroxide OER electrocatalysts in alkaline solution (table S1) and being comparable with the most active transition metal sulfide/phosphide OER electrocatalysts reported so far (11,32,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). To further clarify the structural evolution of Ni nodes in Br-Ni-MOF hollow prisms during OER, the WT-EXAFS analyses under increasing applied potentials were provided, which is helpful for discriminating the backscattering atoms around central metal sites and then evidently determining the exact active structure.…”
Section: Evaluation Of Electrocatalytic Performancementioning
confidence: 79%
“…4F). On the basis of the aforementioned electrocatalytic performance results, the Br-Ni-MOF hollow prisms manifest excellent OER performance with a low  10 , a small Tafel slope, and high TOF values after an in situ activation process, serving as one of the most efficient MOF-based or MOF-derived (oxy)hydroxide OER electrocatalysts in alkaline solution (table S1) and being comparable with the most active transition metal sulfide/phosphide OER electrocatalysts reported so far (11,32,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). To further clarify the structural evolution of Ni nodes in Br-Ni-MOF hollow prisms during OER, the WT-EXAFS analyses under increasing applied potentials were provided, which is helpful for discriminating the backscattering atoms around central metal sites and then evidently determining the exact active structure.…”
Section: Evaluation Of Electrocatalytic Performancementioning
confidence: 79%
“…Other structurally distinct MOFs constructed from nickel‐based nodes and pyrazolate‐based linkers, such as PCN‐601 and PCN‐602 (Figures (b) and 4(c)) , have also been reported to show remarkable chemical stability in strong alkaline solutions and PBS. A recent study also shows that the crystallinity of MOFs constructed from nickel‐ and cobalt‐based nodes and triazole‐based linkers can be preserved after both immersion and electrochemical operation in strong alkaline solutions . We thus believe that in future studies, such MOFs constructed from pyrazolate‐ or triazole‐based linkers with exceptionally high chemical stability will be attractive candidates as the active materials for electrochemical sensing applications, especially for those requiring the operations in alkaline media or phosphate‐containing biological environments.…”
Section: Chemically Stable Mofsmentioning
confidence: 97%
“…(NH 4 ) 3 [Nb­(O 2 ) 4 ] showed a signal at −1522 ppm (Figure S2a). It was observed that only Nb-OC@TBAF-0.5 showed two resonance signals appearing at a lower field (Figure S2b), while Nb oxo-clusters obtained using TBACl, TBAHSO 4 , and TBAOAc showed only a similar resonance signal at −1288, −1322, and −1340 ppm, respectively (Figure S2c–e), which implied that these anions only showed a weak coordination ability to Nb sites in comparison with F – ions. …”
Section: Resultsmentioning
confidence: 98%